Specific of interaction of the macroparticles with the plasma-beam systems - Bizyukov, A.A.; Chibisov, A.D.; Romashchenko, E.V.; Masich, V.V. (Вопросы атомной науки и техники, 2021)
The presented paper summarizes the results of the last works of the authors on modeling the processes of heating and evaporation of macroparticles in a plasma-beam system. The emphasis are made on the influence of the parameters of the plasma as well as the electron beam introduced into the plasma on these processes. A detailed analysis of the effects that accelerate or slow down the rate of heating and evaporation of macroparticles has been performed.